Hepatitis C virus diagnosis using microfluidics technique - Fahmi, Samsuri; Ezhilnavaroji, Jeroish Zachariah; Narayanamurthy, Vigneswaran; Shanmugavel, Bhuvaneshwari Kumaravel (2021)
Conventional techniques for HCV detection required highly sophisticated equipment, huge samples, reagents, and human resources and highly timeconsuming. Rapid test kits detect only HCV Ab and even after no active infection, antibodies can be detected. In RNA detection, filtering of unwanted particles in blood is difficult. Filtration can be achieved using the suitable grade filter paper. The overall results reveal that the large particles are filtered, and HCV particles alone reached the outlet to commence the RT-LAMP reaction.